Aproximación fractal para semivariogramas freáticos - Mercado E., José R. (2002)
Hausdorff’s measure is integrated upon, and Hölder’s exponent is obtained as the codimension DT ? D of the fractal in the Euclidian space in which it is immersed. This has resulted from the application of Daniell’s integral conception, which makes it possible to integrate Lipschitz’s and Hölder’s functions into Baire’s measures and to define fractal space with Hutchinson’s metric. The power for the potentiated model of the semivariograms of stationary processes is obtained. It is applied to the levels of the phreatic strata of Valle del Carrizo, Sinaloa, Mexico, and the experimental semivariograms, and those of the adjustment with a potential model are created, with the finding that its power is = 1,5. It is also found that the fractal dimension of these strata is 2,25.